2007
DOI: 10.1111/j.1365-2559.2007.02719.x
|View full text |Cite
|
Sign up to set email alerts
|

Advances in salivary gland pathology

Abstract: This review summarizes the new findings on salivary gland pathology under the following categories: immunohistochemistry; molecular genetics; newly recognized tumour types; known tumour entities with new findings; and progression of salivary gland tumours. In the application of immunohistochemistry, CD117 can aid in highlighting the luminal cell component of various salivary gland tumours, whereas p63 or maspin can aid in highlighting the abluminal cell component. A high Ki67 index remains the most useful mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
180
3
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(196 citation statements)
references
References 130 publications
(249 reference statements)
5
180
3
8
Order By: Relevance
“…Dedifferentiation in the form of high-grade sarcomatoid tumor has been documented in nearly every type of salivary gland carcinomas [3,8,[10][11][12][13]. Our case must be distinguished cautiously from dedifferentiated MEC [7,14].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Dedifferentiation in the form of high-grade sarcomatoid tumor has been documented in nearly every type of salivary gland carcinomas [3,8,[10][11][12][13]. Our case must be distinguished cautiously from dedifferentiated MEC [7,14].…”
Section: Discussionmentioning
confidence: 81%
“…In addition to the multiplicity of cell types, complex and varied architectural patterns are also the hallmark of MEC [2]. Although several histologic variants have been proposed [1][2][3][4], MEC seldom consists of a predominant population of spindled cells [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, definitive evidence in this regard will have to await further study. Of interest is the discovery within the last few years that most MECs exhibit a t(11:19)(q21:p13) translocation resulting in the MECT1:MAML2 fusion protein [41][42][43][44]. Recently, this translocation has also been reported in CMEC [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…While it is not clear that they are related, there have also been tumors with similar morphology labeled ''salivary duct carcinoma in situ'' in the literature [4]. Currently the World Health Organization (WHO) classifies these tumors as a variant of cystadenocarcinoma, which has generated some controversy, with some authors still believing that they represent a ductal tumor [8,13]. Wayne et al compared IDC to cystadenocarcinoma, NOS, in abstract form at the United States and Canadian Academy of Pathology's (USCAP) annual meeting and found some overlap between these tumors and concluded that they were more closely related to eachother than to conventional salivary duct carcinoma (SDC) [7].…”
Section: Discussionmentioning
confidence: 99%